Analisis Sistem Manajemen Inventori Material Konstruksi Berbasis Cloud dan Real-Time - Yuantomi Rohmat Udin; Dika Puspitaningrum (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
The construction industry faces major challenges in managing material inventory, particularly among start-up companies that still rely on paper-based manual records. Such practices often lead to data inconsistencies, delays in decision-making, and project inefficiencies. This study aims to analyze the implementation of a cloud-based and real-time inventory management system utilizing spreadsheets at PT X, a start-up contractor located in Karanganyar, Central Java. The research employs a qualitative case study approach, with data collected through direct observation, semi-structured interviews with finance staff, logistics administration staff, and the project manager, as well as documentation of material inflows and outflows. The findings reveal that the use of cloud-based spreadsheets enhances data transparency, facilitates real-time monitoring between field and office, and accelerates stock opname validation. The system also supports more responsive decision-making regarding material reordering and request postponements. Nevertheless, several obstacles remain, including limited digital literacy among staff, potential input errors, and reliance on internet connectivity. Theoretically, this research contributes to the literature on accounting information systems and inventory management in small-scale construction sectors. Practically, it demonstrates that low-cost cloud solutions can improve operational efficiency and serve as a foundation for developing more integrated systems in the future.